1999
DOI: 10.1016/s0014-5793(98)01701-3
|View full text |Cite
|
Sign up to set email alerts
|

The lipopolysaccharide‐binding protein participating in hemocyte nodule formation in the silkworm Bombyx mori is a novel member of the C‐type lectin superfamily with two different tandem carbohydrate‐recognition domains1

Abstract: We recently isolated and characterized the lipopolysaccharide (LPS)-binding protein, BmLBP, from the larval hemolymph of the silkworm Bombyx mori. BmLBP is a pattern recognition molecule that recognizes the lipid A portion of LPS and participates in a cellular defense reaction. This paper describes the cDNA cloning of BmLBP. The deduced amino acid sequence of BmLBP revealed that BmLBP is a novel member of the C-type lectin superfamily with a unique structural feature that consists of two different carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 22 publications
2
112
0
Order By: Relevance
“…It contains two C-type CRDs, an amino-terminal domain, CRD1 (residues 1-136), and a carboxyl-terminal domain, CRD2 (residues 137-288). This feature of IML-2 is similar to another M. sexta lectin, immulectin (now designated IML-1) (16), and to lectins from other two insect species: LPS-binding proteins from the silkworm, B. mori (15), and the fall webworm, H. cunea (18). Fig.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…It contains two C-type CRDs, an amino-terminal domain, CRD1 (residues 1-136), and a carboxyl-terminal domain, CRD2 (residues 137-288). This feature of IML-2 is similar to another M. sexta lectin, immulectin (now designated IML-1) (16), and to lectins from other two insect species: LPS-binding proteins from the silkworm, B. mori (15), and the fall webworm, H. cunea (18). Fig.…”
Section: Resultssupporting
confidence: 53%
“…We have isolated from plasma of the tobacco hornworm, M. sexta, a C-type lectin, IML-2, that binds to Gram-negative bacteria and stimulates phenol oxidase activation. IML-2 contains two CRDs, an organization that is similar to that of immulectin-1, another C-type lectin from M. sexta (16), and C-type lectins from two other lepidopteran insect species, B. mori (15) and H. cunea (18). M. sexta IML-2 is 55% identical in sequence to B. mori lipopolysaccharide-binding protein, 47% identical to H. cunea lectin, and only 27% identical to M. sexta IML-1.…”
Section: Binding Of Iml-2 To Lps -A Candidate Ligand For Iml-2 Ismentioning
confidence: 99%
See 2 more Smart Citations
“…The deduced amino acid sequence of H. cunea lectin showed a signi¢cant similarity with the lipopolysaccharide (LPS) binding protein of the American cockroach, that is related in sequence to the C-type lectins of vertebrates [3,4]. Recently, the studies of BmLBP (LPS binding protein from Bombyx mori) and immunolectin revealed that they contain two di¡erent CRDs [5,6]. The amino acid sequence alignment of H. cunea lectin, BmLBP and immunolectin shows that C-type lectins with two CRDs are conserved in three lepidopterian insects, H. cunea, B. mori and Manduca sexta (Fig.…”
Section: Introductionmentioning
confidence: 99%